Morphological Changes of the Morphometric Parameters of the Gastric Mucosa Under the Influence of Polipragmasia in Five-Month-Old Purebred Rats - Norbekovich, Toshmamatov Bakhtiyor; Eshmamatovna, Djumanova Nargiza (American Journal of Biology and Natural Sciences, 2024)
During the COVID-19 pandemic, excessive polypharmacy was allowed to improve the condition of in- fected patients, reduce body temperature, improve breathing, help with sputum withdrawal, relieve bone pain, etc., the causes of disability are also the result of unjustified use of drugs. A one-sided approach to prescribing is the leading cause of mortality and disability. The risk of polypharmacy is higher in vulnerable groups, including those with pre-existing conditions such as diabetes and rheumatic diseases, as well as older patients.